Translation as rewriting with ideological and cultural turns: a comparative analysis of the translators' subjectivity based on two translated versions of The Grapes of Wrath - Chew, Chia Meng (Nanyang Technological University, 2022)
The Grapes of Wrath is one of the most enduring realist novels in the American literary canon. John Steinbeck wrote this novel in April of 1939 which immediately received critical acclaim and took the world by storm. The Grapes of Wrath has been translated into Chinese, and there are two main versions available in the market, viz. the mainland Chinese version by Shanghai Translation Publishing House (2001) and the Chinese Taiwanese version by Spring International Publishers Co. Ltd. (2013). Cultural elements and colloquial expressions that are typical of the English language used in the U.S.A. of the 1930s and 1940s abound in The Grapes of Wrath, which invariably make their translation challenging. It is, therefore, worth further academic research into how such use of language is treated and translated in the two versions of the translation in terms of stylistic and linguistic similarities and dissimilarities, and how this, in turn, impacts and influences the final output of translation. Using primarily the theories of André Lefevere (1992) as propounded in one of his works, Translation, Rewriting, and The Manipulation of Literary Fame, stylistic and linguistic subtleties in the source text are further analyzed to determine how a translator’s subjectivity can play a role in delivering the intended meaning of the author and the extent to which such subjectivity can dictate the translation, at both semantic and pragmatic levels. Such semantic and pragmatic interpretations of the source text by a translator often have a profoundly implicative effect on the final translation output, which either effectively conveys, transcends, or deviates from the intended meaning of the author. This paper delves into how such subjectivity in translation, albeit subliminal on the part of the translators, is governed and manipulated by their own ideologies and the various cultural turns that they have been subjected to in various stages of their lives.